Hijrah in Style: Surabaya Muslim Women, Hijab Practices, and the Fashioning of Identity - Meyrasyawati, Dewi (Journal of Advanced Research in Humanities and Social Sciences; Vol 12 No 1 (2025): Journal of Advanced Research in Humanities and Social Sciences, 2025)
The term hijrah, originally referring to the Prophet Muhammad’s migration from Mecca, has evolved in contemporary Indonesia to signify a spiritual transformation, often linked to religious practices and attire changes. One prominent expression of this shift is the adoption of hijab shar’i, a veiling style that emphasises modesty and adherence to Islamic teachings. In Surabaya, some Muslim women actively promote hijab shar’i as part of their hijrah, associating it with religious commitment and identity formation. This study examines how hijab shar’i functions as both a fashion statement and a symbolic boundary marker of religious identity. Drawing on Malcolm Barnard’s fashion theory, this research explores the intersection of fashion culture, lifestyle, and religious expression among Muslim women. Employing field observations and in-depth interviews, the findings reveal a shifting interpretation of hijrah—not merely as a spiritual journey but also as a dynamic process influenced by sociocultural and fashion trends. The study highlights how hijab shar’i wearers negotiate their identity within the broader discourse of Indonesian Muslim fashion, challenging conventional binaries of piety and modernity. By situating hijab shar’i within fashion culture and lifestyle studies, this research contributes to a nuanced understanding of religious dress as a form of self-expression and boundary-making in an increasingly globalised world.